Growth and health performance of pacific white shrimp fed diets with varying protein levels and citral supplementation - Paramadina, Siwi; Ekasari, Julie; Agus Suprayudi, Muhammad; Achmad Fauzi, Ichsan; Shofa Adestia, Talita (Jurnal Akuakultur Indonesia, 2025)
Citral is known for its antimicrobial, antioxidant, and anti-diabetic properties. This study evaluates the effects of dietary citral supplementation on glucose absorption, growth, feed utilization, and health of Pacific white leg shrimp (Litopenaeus vannamei) fed different protein levels. A 2×3 factorial experiment was conducted with two variables: protein content (30% and 35%) and citral concentrations (0, 50, and 75 mg/kg). Shrimp (3.22 ± 0.01 g) were reared in 180 L tanks (30 shrimp/tank) for 60 days. Citral supplementation increased blood glucose levels in the first two hours post-feeding, with a faster return to basal levels. Growth and feed efficiency also improved with citral diets. After stress testing, citral and dietary protein showed a synergistic effect on superoxide dismutase (SOD), with the highest level in the 75 mg/kg citral, 35% protein diet, correlating with higher post-challenge survival. Total haemocyte count (THC), phenoloxidase (PO) activity, respiratory burst (RB), and blood clotting time improved with citral supplementation, while protein level only affected RB. After Vibrio challenge, higher protein increased THC and reduced clotting time, while citral enhanced THC, PO, and RB. The highest post-challenge survival was observed in shrimp fed 75 mg/kg citral with 35% protein (p